Cause Analysis and Diagnosis and Treatment of Intestinal Fistulas After Ultrasound-Guided Microwave Ablation of Abdominopelvic Lesions - Tan, Shuilian; Yu, Xiaoling; Cheng, Zhigang; Zhang, Jing; Yu, Jie; Liu, Fangyi; Gao, Yuanjin; Linghu, Runze; Han, Zhiyu; Liang, Ping (Frontiers in Surgery, 2021)
Objective: To determine the cause and high-risk factors for the development of intestinal fistulas (IFs) after ultrasound-guided microwave ablation (MA) of abdominopelvic lesions, and to identify effective prophylactic and therapeutic actions. Methods: Clinical data were collected from patients with an intestinal fistula (IF) after ultrasound-guided MA of abdominopelvic lesions in our hospital from January 1, 2010 to December 31, 2018. The cause, diagnosis, and treatment of IFs in these patients were analyzed. Results: Among 8969 patients who underwent ultrasound-guided MA of abdominopelvic lesions, eight patients developed IF after MA，seven patients were discharged after being cured and one died. Conclusion: Abdominopelvic lesions are close to the intestines, so histories of surgery, radiotherapy, and abdominopelvic infection are high-risk factors for IF development after MA of these lesions. Surgical treatment should be provided as soon as an IF is identified.